Carbon and Oxygen Isotope Studies in Marbles - Sheppard, Simon Mark Foster (My University, 1966)
Fractionations of C^13/C^12, O^18/O^16 ratios and Mg between coexisting dolomite and calcite have been determined from rocks of a variety of metamorphic grades in Vermont and the Grenville of Ontario. Working criteria for equilibrium are established. Temperature dependent fractionation expressions are derived (1) for O^18 and C^13 from the C-and O-isotope fractionations concordant with the Mg-calcite solvus thermometer, for T = 130° to 550°C, using natural dolomite-calcite assemblages; (2) for C^13 from hydrothermal partial exchange experiments. Problems with partial exchange reactions are discussed. A thermodynamic analysis of the solvus relations shows that spinodal decomposition probably is important in high Mg-calcites. Quench phenomena in high grade assemblages are complex. The quench temperature may be much lower than the maximum temperature attained. The sizes of some equilibrium systems are delineated.
Keywords: carbon, oxygen, isotope, marbles, temperature, reactions